Teachers’ Voices on the Challenges of the Implementation of Communicative Approach in Regards to the 2013 Curriculum - Yenni Rahmawati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThe Indonesian ELT current curriculum (the 2013 Curriculum) adopts communicative Approach (CA) as its basis foundation. Despite the fact that this approach has been adopted for some years, some research studies showed that it does not bring any significant improvement to the learner’s outcome. There are several reasons underpinning the failures of the implementation of CA in regards to the 2013 curriculum. This study is, therefore, aimed at investigating the EFL Indonesian teachers’ perspectives on the challenges they faced in the implementation of communicative approach in their classrooms along with the 2013 curriculum. Four participants were involved in this study that were given questionnaires and interviewed for data collection. Qualitative design by case study was used in this study and the results indicated that all teachers in this study encountered challenges when implementing the concept of CA along with the 2013 curriculum, i.e. students’ low motivations, the teachers’ role, the class size, the teachers’ income, and the availability of English materials.ABSTRAKKurikulum Bahasa Inggrisdi Indonesia saat ini (Kurikulum 2013) mengadopsi Pendekatan Komunikatif (CA) sebagai landasan dasarnya. Terlepas dari kenyataan bahwa pendekatan ini telah diadopsi selama beberapa tahun, beberapa penelitian menunjukkan bahwa Pendekatan Komunikatif tidak membawa dampak yang signifikan terhadap hasil pelajar. Ada beberapa alasan yang mendasari kegagalan implementasi CA tersebut terkait kurikulum 2013. Oleh karena itu, penelitian ini bertujuan mengeksplorasi perspektif guru bahasa Inggris di Indonesia tentang tantangan yang mereka hadapi dalam menerapkan pendekatan komunikatif di ruang kelas mereka dalam kerangka kurikulum 2013. Empat peserta terlibat dalam penelitian ini yang diberi kuesioner dan diwawancarai untuk pengumpulan data. Penelitian ini menggunakan desain kualitatif dengan studi kasus dan hasilnya menunjukkan bahwa semua guru dalam penelitian ini menghadapi tantangan ketika menerapkan konsep CA bersama dengan kurikulum 2013, yaitu motivasi siswa, peran guru, 'konten asing' , dan ketersediaan materi bahasa Inggris. How to Cite: Rahmawati, Y. (2019). Teachers’ Voices on the Challenges of the Implementation of Communicative Approach in Regards to the 2013 Curriculum. IJEE (Indonesian Journal of English Education), 6(1), 65-78. doi:10.15408/ijee.v6i1.12761